Understanding Audit and Feedback to Support Falls Prevention and Pain Management in Home Health Care. (May 2016) - Gifford, Wendy; Davies, Barbara; Rowan, Margo; Egan, Mary; Lefebre, Nancy; Brehaut, Jamie A.
Audit and feedback (A&F) is commonly used to improve health care; yet enormous variability exists in effectiveness and little is known about A&F in home health care. This article explores A&F as a strategy to support evidence-based care for falls prevention and pain management. We use interviews to describe how A&F is currently used and explore how it can support patient care. Thirteen interviews were conducted with a multidisciplinary sample and descriptively analyzed. Findings showed that data were audited by frontline staff but were inconsistently fed back to the front line, and the meaning of data depended on the context and participants' roles. Findings suggest A&F should include indicators to benchmark patient outcomes, target actionable processes of care, and be tailored to provider groups.